The Relationship Between Excessive Screen Time and Children's Frustration Tolerance During Learning: Addressing the Link Between Habitual Instant Gratification and the Tendency to Give Up or Cry - Deiby Kambey (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2026)
Excessive screen time in early childhood has become a crucial issue impacting socio-emotional development, particularly frustration tolerance. Children accustomed to the instant gratification provided by digital devices tend to face difficulties when dealing with learning challenges that require a process. This study aims to analyze the relationship between the duration of screen time and the ability of children aged 6–7 years to manage emotions and frustration during private tutoring sessions. The research method employed is descriptive qualitative, with data collection techniques consisting of observation, direct participatory observation, and field notes compiled over four months of private sessions (Mondays, Tuesdays, and Wednesdays from 09:00 to 10:00 WIB). The results of the analysis indicate that screen time exceeding the World Health Organization (WHO) recommended limits is closely correlated with increased defensive behavior, decreased concentration, and self-defense mechanisms—such as crying or throwing negative accusations at the tutor—when encountering difficulties in literacy and numeracy (calistung). It is concluded that parental supervision of screen duration and the implementation of emotion regulation by private tutors are key factors in moderating the negative impacts of screen time on children's learning readiness.